2017
DOI: 10.1155/2017/1308217
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Si3N4-Based Artificial Basilar Membrane with ZnO Nanopillar Using MEMS Process

Abstract: This paper presents the fabrication of Si 3 N 4 -based artificial basilar membrane (ABM) with ZnO nanopillar array. Structure of ABMs is composed of the logarithmically varying membrane fabricated by MEMS process and piezonanopillar array grown on the Si 3 N 4 -based membrane by hydrothermal method. We fabricate the bottom substrate containing Si 3 N 4 -based membrane for inducing the resonant motions from the sound wave and the top substrates of electrodes for acquiring electric signals. In addition, the bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It is key that the device has a trapezoidal shape mimicking the basilar membrane and displays piezoelectric properties. It has been shown that a trapezoidal membrane [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] or an array of beams with various lengths [ 30 , 31 , 32 , 33 , 34 , 35 ] can realize frequency selectivity over a wide range of local resonance frequencies. Piezoelectric materials generate electrical signals in response to an external force making them applicable to fully implantable cochlear implants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is key that the device has a trapezoidal shape mimicking the basilar membrane and displays piezoelectric properties. It has been shown that a trapezoidal membrane [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] or an array of beams with various lengths [ 30 , 31 , 32 , 33 , 34 , 35 ] can realize frequency selectivity over a wide range of local resonance frequencies. Piezoelectric materials generate electrical signals in response to an external force making them applicable to fully implantable cochlear implants.…”
Section: Introductionmentioning
confidence: 99%
“…Shintaku et al [ 36 ] have shown that poly(vinylidene fluoride–trifluoroethylene) (P(VDF-TrFE)) films are biocompatible and have low toxicity for the human body. In addition, polyvinylidene difluoride (PVDF) [ 22 , 23 , 25 , 29 , 33 , 35 ], lead zirconate titanate (PZT) [ 24 , 34 ], zinc oxide [ 26 ], and aluminum nitride [ 30 , 31 , 32 ] have also been applied in previous studies. Our and a few research groups have experimentally observed electrically evoked auditory brainstem responses (eABRs) with fully implantable artificial cochleae to evaluate their potential for clinical application [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of developing such implants is based on biomimetics, with the key functions being the frequency selectivity of the basilar membrane and the conversion of sound/electrical signals of the inner hair cells. Commonly used methods for reproducing the frequency selectivity include the fabrication of trapezoidal membranes [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] and beams of different lengths [ 19 , 20 , 21 , 22 , 23 , 24 ]. Organic piezoelectric materials made of polyvinylidene difluoride (PVDF) [ 10 , 11 , 13 , 17 , 18 , 24 ] or poly(vinylidene fluoride-co-trifluoroethylene) (PVDF-TrFE) [ 25 ] and inorganic materials comprising lead zirconate titanate [ 12 , 23 ], zinc oxide [ 14 ], and aluminum nitride [ 19 , 20 , 21 ] have been used for sound/electrical signal conversion.…”
Section: Introductionmentioning
confidence: 99%
“…For future clinical applications, micro‐machined cochlea must show frequency selectivity and be able to convert mechanical oscillations into electrical signals. Frequency selectivity has been achieved by using trapezoidal membranes 3,4,8‐12 and arrays of beams with different lengths 15‐20 to allow a variable local resonance frequency. Piezoelectric materials convert mechanical deformations into electric potentials via the piezoelectric effect and have been commonly used in micro‐machined cochleae 3,4,8‐12,15‐20 .…”
Section: Introductionmentioning
confidence: 99%
“…Frequency selectivity has been achieved by using trapezoidal membranes 3,4,8‐12 and arrays of beams with different lengths 15‐20 to allow a variable local resonance frequency. Piezoelectric materials convert mechanical deformations into electric potentials via the piezoelectric effect and have been commonly used in micro‐machined cochleae 3,4,8‐12,15‐20 . Although Shintaku et al 19 have shown that poly(vinylidene fluoride–trifluoroethylene) (P[VDF‐TrFE]) films are biocompatible and have low toxicity for humans, organic piezoelectric materials generally have a lower efficiency.…”
Section: Introductionmentioning
confidence: 99%